2017
DOI: 10.7251/her2117107p
|View full text |Cite
|
Sign up to set email alerts
|

Трендови Индекса Екстремних Температура У Босни И Херцеговини ‒ Примјер Мостара

Abstract: Сажетак: У раду су анализирани трендови индекса екстремних температура у Босни и Херцеговини. Дневне минималне и максималне температуре у периоду . године са метеоролошке станице Мостар (који је изабран за студију случаја) коришћене су за израчунавање 18 индекса употребом RClimDex (1.0) софтвера. Максималне и минималне температуре показују тенденцију раста током цијеле године. Позитивни трендови топлих температурних индекса израженији су од опадајућих трендова хладних температурних индекса. Међутим, оба тренда… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
1
5
0
2
Order By: Relevance
“…It can be concluded that the observed increasing warming tendency was more the result of rising frequency warm indices extremes than the reduction in frequency of cold ones. The stated is in accordance with the results of the previous studies carried out in Bosnia and Herzegovina which determined that the warming trend was the strongest in the summer season (Popov et al, 2017a;Trbic et al, 2017) and follows the results of the other studies carried out in the Southeast Europe region (Branković et al, 2013;Burić et al, 2014;Knežević et al, 2014). Similar trends in the temperature indices based on fixed thresholds were found globally (Alexander et al, 2006) and in Europe at the continental scale (Klein Tank & Können, 2003).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It can be concluded that the observed increasing warming tendency was more the result of rising frequency warm indices extremes than the reduction in frequency of cold ones. The stated is in accordance with the results of the previous studies carried out in Bosnia and Herzegovina which determined that the warming trend was the strongest in the summer season (Popov et al, 2017a;Trbic et al, 2017) and follows the results of the other studies carried out in the Southeast Europe region (Branković et al, 2013;Burić et al, 2014;Knežević et al, 2014). Similar trends in the temperature indices based on fixed thresholds were found globally (Alexander et al, 2006) and in Europe at the continental scale (Klein Tank & Können, 2003).…”
Section: Resultssupporting
confidence: 91%
“…Previous studies on mean temperatures determined that the climate system warming had been present over the territory of Bosnia and Herzegovina throughout the year (most prominent in summer season) (Trbić, Popov, & Gnjato, 2017). However, a comprehensive research on trends in the extreme temperature indices based on fixed thresholds has not been carried out so far for this area, although a few studies (Popov, Gnjato, & Trbić, 2017a;2017b) have partially addressed this issue. The main goal of this study is to analyze trends in both warm and cold indices based on fixed thresholds over Bosnia and Herzegovina using five internationally agreed extreme temperature indices for the recent climate change assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on climate change over this area have shown that there is a warming tendency over the study area (Popov et al, 2017(Popov et al, , 2018a(Popov et al, , 2018b(Popov et al, , 2019bTrbić et al, 2017). The загријавања (Popov et al, 2017(Popov et al, , 2018а, 2018b(Popov et al, , 2019bTrbić et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…У Мостару су, на примјер, у периоду 1961−2015. године средња максимална и средња минимална температура значајно порасле за 0.3°C по деценији (Popov et al, 2017, док су апсолутно максимална и апсолутно минимална температура ваздуха значајно порасле за 0.5°C по деценији и 0.4°C по деценији, респективно (Popov et al, 2018b). Истраживања су утврдила да су трендови индекса екстремних температура били израженији за индексе добијене на основу максималних температура (Popov et al, 2017), што указује да је на овом простору пораст максималних температура ваздуха већи од пораста минималних температура.…”
Section: Introductionunclassified
“…A similar trend continued in the next century, so the four warmest years since instrumental measurements were recorded in the second decade of the 21 st century -2015century - , 2016century - , 2017century - and 2018century - (WMO, 2019. Previous research into climate change in the wider region and in Southeast Europe has addressed similar issues (Jovanović et al, 2002;Unkašević & Tošić, 2013;Tosić et al, 2016;Trbić et al, 2017;Gavrilov et al, 2015;Gavrilov et al, 2016;Gavrilov et al, 2018;Ivanović et al, 2016;Popov et al, 2017; * Corresponding author: nikola.bacevic@pr.ac.rs al., 2018;Vukoičić et al, 2018;Papić et al, 2019) and aridity as an indicator of climate change (Hrnjak et al, 2014;Radaković et al, 2017;Milentijević et al, 2018). A statistically significant upward trend in the average annual air temperature was also observed in the urban area (Savić et al, 2013;Bačević et al, 2018).…”
Section: Introductionmentioning
confidence: 91%